ABET accreditation requirements and preparation: Lessons learned from a case study of Civil Engineering Program. Issue 1 (1st January 2021) - Alhorani, Rana A. M.; Abu Elhaija, Wejdan; Bazlamit, Subhi M.; Ahmad, Hesham S.
Abstract: With the need for specialized civil engineers rising in local and regional markets, Al-Zaytoonah University of Jordan (ZUJ) had launched the Civil and Infrastructure Engineering (CIE) program in 2009. The CIE program has aspired to be among renowned universities worldwide through the recognition of the Accreditation Board for Engineering and Technology (ABET). The CIE curriculum was adapted to meet the requirements of ABET. As a consequence of preparing for the first-time accreditation of the CIE program, the authors have learned several valuable lessons. This article constitutes a roadmap to those seeking first-time ABET (or other) engineering accreditation for their programs by reviewing the work of other successful first-time accreditation efforts and analyzing similar processes that were necessitated at ZUJ in preparation for the accreditation. In particular, the article describes the processes used and corresponding results of the ABET Site Visit completed in November and provides a good resource for conducting a sustainable continuous improvement process. Throughout the self-assessment process, feedback was gathered and information was solicited from internal and external formal/informal sources. Periodic collections of specific inputs regarding the program educational objectives, curriculum, and outcomes were requested through meetings, discussions, questionnaires and archives of the CIE Department in the period from 2016 to 2019. Data analysis was performed using Likert scale, statistical analysis, qualitative analysis and judgment to evaluate and perform the necessary reviews and revisions in the accreditation process.